Application of Cartographic Modelling as a research method when monitoring the spatial behaviour of population - Pribytkova, I. (Социология: теория, методы, маркетинг, 2015)
There is presented the cartographical modeling as efficient method to monitor the spatial behaviour of population. The author examines the common notion of a method, the cognition properties of cartographical models and necessary methodical premises to ensure an adequate representation of essential features of the population’s spatial behaviour or other investigated phenomena (processes, structures). In the author’s opinion the cartographical modeling may be regarded as one of the modifications of latent structure analysis which is able to reveal and distinguish the latent groups of population with peculiar social organization, material and cultural consumption, goals, preferences and behaviour. There are demonstrated the cartographical models of spatial disposition of rural population in able-bodied age in Ukraine which give a clear view of the geographical location of rural inhabitants and their concentration or dispersion in certain regions of countryside. These models discover the important spatial relations between movements of rural inhabitants and urbanization in Uk raine. Comparing these models we come to the conclusion that concentration of urban and concentration of rural population within the bounds of the Ukraine are two sides of one and the same process of urbanization. In this process, towns and cities perform the duties of peculiar nuclei for crystallization of new socio-spatial structures of rural resettling. The demographic consequences of spatial self-organization of country people are highly various, closely tied and are displayed first of all in different types of dynamics. With a view to investigate the types of population changes in the country side of Ukraine in 1970–1978 — in a moment when the demographic transition was over — the author elaborated the cartograms with types of rural population dynamics after J. W. Webb’s model. It is obvious that the depopulation and migratory losses brought about the irreparable consequences for rural population practically in all regions of Ukraine.